Mechanical test and action mechanism of interface between gravel soil and concrete - Du, Peng; Zhou, Dequan; Liu, Xiaoling; Chen, Xin (Frontiers in Earth Science, 2023)
The mechanical properties of the gravel soil-concrete structure interface are one of the important issues in academia and engineering. In this research, gravel soil samples were collected from the Three Gorges Reservoir region to carry out simple shear and direct shear tests of the gravel soil-structure interface. The shearing process was simulated with the numerical method. The strength and deformation characteristics of the interface, the applicability of the interface constitutive model, and the failure mechanism of the interface were analyzed. The results show that: (1) The direct shear test curve of the gravel soil-concrete interface shows strain softening with obvious stress peak, while the simple shear test curve shows strain hardening. The stress peak of the direct shear test is about 30% higher than that of the simple shear test. The shear contraction effect of the simple shear test is about 31% larger than that of the direct shear test. (2) The nonlinear relationship of the gravel soil-concrete interface can be described by a hyperbola model, which has a good adaptability to the constitutive relationship of the interface in numerical analysis software.(3) The gravel soil-concrete interface gradually develops shear failure from the edge to the inside. The essence of soil-structure interaction is the movement of soil grains. The research results can provide a reference for the analysis of gravel soil-concrete interaction.